Invaginacija slepiča kot posledica endometrioze - Kruh, Vasja (Zdravniški vestnik, 2003)
Background. Invagination of the vermiform appendix is a very rare occurrence. We summarize epidemiologic and etiologic factors, types of classification, symtomatology, diagnostic features and treatment. Patients and treatment. The authors present 49 years old female with long-standing abdominal pains, who came in our hospital due to acute exacerbation with sever abdominal pain. Because of progressive symptoms and sensitivity in the right-lower abdominal quadrant a diagnostic laparoscopy was performed. An anomaly of cecum and the absence of appendix vermiformis have forced us to proceed with laparotomy in McBurnay point. After cecotomy an invaginated gangrenous appendix was found. The histological examination revealed endometriosis. Conclusions. By presenting this extremely rare pathology we also want to emphasize the important role of diagnostic laparoscopy in front of acute abdomen.
Keywords: Abdomen, Acute; Adult; Apendiks; Appendix; Cecal Diseases; Cekalne bolezni; Complications; Endometriosis; Endometrioza; Intussusception; Intususcepcija; Odrasli; Trebuh, akutni